The paradigm of paraglacial megafans of the San Juan river basin, Central Andes, Argentina - Suvires, Graciela Mabel (2014)
The spatial distribution and several morphometric characteristics of the Quaternary alluvial fans of the San Juan River, in the province of San Juan, at the Central and Western part of Argentina, have been studied to classify them as paraglacial megafans, as well to ratify its depositional environmental conditions. The high sedimentary load exported by San Juan river from the Central Andes to the foreland depressions is estimated about 3,682,200 hm3. The large alluvial fans of Ullum-Zonda and Tulum valleys were deposited into deep tectonic depressions, during the Upper Pleistocene deglaciation stages. The outcome of collecting remotely sensed data, map and DEM data, geophysical data and much fieldwork gave access to morphometric, morphographic and morphogenetic data of these alluvial fans. The main drainage network was mapped on processed images using QGis (vers.2.0.1). Several fan morphometric parameters were measured, such as the size, the shape, the thickness, the surface areas and the sedimentary volume of exported load. The analyzed fans were accumulated in deep tectonic depressions, where the alluvium fill reaches 700 to 1200 m thick. Such fans do not reach the large size that other world megafans have, and this is due to tectonic obstacles, although the sedimentary fill average volume surpasses 514,000 hm3. The author proposes to consider Ullum-Zonda and Tulum alluvial fans as paraglacial megafans. According to the stratigraphic relationships of the tropical South American Rivers, the author considers that the San Juan paraglacial megafans would have occurred in the period before 24 ka BP , possibly corresponding to Middle Pleniglacial (ca 65-24ka BP). They record colder and more humid conditions compared with the present arid and dry conditions.